Las costumbres en el imaginario literario de la comunidad de Chumillos Altos, Cantón Cayambe - García Cobacango, Blanca Azucena (2023)
The aim of this research is to analyze customs from the oral collected stories from Chumillos Altos, Cayambe canton. Through orality, different customs had been maintained and transmitted; but today oral narratives have been devalued and therefore they have been disappearing little by little. To complete this work, similar works research antecedents were used and a theoretical framework, rich in details about orality, literary imaginary and customs was proposed. This research has a qualitative, documentary-descriptive approach and the ethnographic and hermeneutic method was used; the first method helps to understand the functioning of cultures and the second helps to make texts interpretations. Next, the classification of the stories was made, the customs were delimited, and a contrast between the literary imaginary and the social imaginary was made considering the customs identified in the oral narratives. Finally, the oral tradition was valued as a means of transmitting the social imaginary through the literary imaginary. The fundamental interest of this research work lies in seeing the relationship between oral narratives with the social imaginary of the individuals of the community in question. In addition, the idea was to revive indigenous knowledge and therefore the customs and identity of Chumillos Altos community. Consequently, this research work contributed to the dissemination of the native original knowledge, that lies in oral stories, to the general population. To conclude, this research presented the value of the social and literary imaginary and the different ways of life of Chumillos community by evidencing the relationship between these imaginaries.